Evaluation of different promoters driving the GFP reporter gene in seaweed Kappaphycus alvarezii - Muh. Alias L. Rajamuddin; A. Alimuddin; Utut Widyastuti; Irvan Faizal (Universitas Gadjah Mada, 2014)
Promoter regulates expression level of foreign gene in transgenic organism. This study was performed to select asuitable promoter as the fi rst step towards production of valuable trait-enhanced seaweed by transgenic technology. Greenfl uorescent protein (GFP) gene was used as a reporter to determine the activity of promoter in seaweed Kappaphycusalvarezii. GFP gene constructs driven by cytomegalovirus (pCMV-GFP), caulifl ower mosaic virus (pCaMV-GFP),medaka β-actin (pmBA-GFP) and Japanese fl ounder keratin (pJfKer-GFP) promoters were introduced by electroporationmethod. Electroporation was performed using a gene pulser (BIORAD) with voltage of 300 V, pulse length of 0.5 ms,pulse numbers of 4, and pulse interval of 0.1 s. Promoter activity was determined by analyzing GFP gene expressionlevel using a fl uorescent microscope. The results showed that CMV regulated highest number of fi lament callus(34.10%±1.49) expressing GFP at medium to strong fl uorescence levels. CaMV promoter had relatively similar activitywith CMV, but lower number of fi lament callus expressing GFP (10.48%±0.25). mBA promoter drove GFP expressionat medium level and similar number of fi lament callus (8.85%±2.31) expressing GFP with CaMV, while JfKer promoterhad lowest activity by means in number of fi lament callus expressing GFP (4.79%±0.26) and GFP expression level. PCRanalysis for transgenic confi rmation showed a DNA band of PCR product from pCMV-GFP and pCaMV-GFP expressingfi lament callus in the same size (about 0.6 kb) with positive control of plasmid. Thus, CMV and CaMV promoters wasan appropriate promoter and foreign gene could be transferred to fi lament callus by electroporation method. Combiningthis achievement with developing a culture method of fi lament callus to be thallus, stable transgenic breeding in K.alvarezii can be feasible.